Implementation Implementation of Buteyko Breathing Technique on the Respiratory Frequency and Oxygen Saturation in Asthma Patients: A Case Study - Prayuni, Elita Trinanti; Kristinawati, Beti (GLOBAL HEALTH SCIENCE GROUP, 2024)
Monitoring respiratory frequency and oxygen saturation in asthma patients is important to evaluate the severity of attacks, assess response to therapy, and detect complications such as hypoxia or respiratory failure. The Buteyko breathing technique is a type of breathing exercise commonly given to patients with asthma. This therapy aims to reduce respiratory frequency, increase CO2 levels, and improve oxygen saturation in asthma patients. Objective to report the effectiveness of implementing the Buteyko breathing technique in reducing respiratory frequency and improving oxygen saturation in asthma patients. Descriptive design with a case study approach with subjects of 2 asthma patients. Sampling was carried out using a purposive sampling technique. The intervention given was Buteyko breathing for 15 minutes. The inclusion criteria set included patients diagnosed with asthma, patients with good vision and hearing function, patients who had never participated in breathing exercises, and those willing to be given the Buteyko technique. The inclusion criteria in this case were patients with a history of heart failure, kidney failure, and smoking. Data were obtained by interview, observation, and viewing patients' medical records. In this case study, instruments included a physical examination sheet, oximetry vital signs monitoring sheet, blood pressure monitor, thermometer, watch, and nursing documentation sheet. Data were analyzed using simple descriptions with average values. There was a decrease in respiratory frequency from 32.5 x/minute before intervention to 23.5x/minute and an increase in the average oxygen saturation value of 92.5% to 98.5%. Buteyko breathing can be applied to reduce asthma symptoms, which are characterized by a decrease in respiratory frequency, an increase in oxygen saturation, and reduced complaints of shortness of breath in patients.